Association between rheumatoid arthritis and systemic mastocytosis: a case report and literature review. Issue 10 (October 2016) - Latar, Ichraq; Koufany, Meriem; Hablot, Julie; Loeuille, Damien; Netter, Patrick; Jouzeau, Jean-Yves; Chary-Valckenaere, Isabelle; Moulin, David
Abstract Classically, mast cells (MC) are considered as important actors of the innate immune response playing a pivotal role in IgE-mediated allergic and antiparasite responses. In the last two decades, many experimental evidences demonstrated that these hematopoietic-derived cells present in both connective and mucosal tissues are also key modulators of the adaptive immune response and could contribute to autoimmune disease notably in rheumatoid arthritis (RA). Recently, Bader-Meunier et al. reported a series of 31 patients suffering from inflammatory joint diseases associated with mastocytosis, suggesting that mastocytosis was associated with a higher prevalence in spondyloarthritis. We discuss here the possible link between chronic inflammatory arthritis and mastocytosis through the report of a clinical case describing a patient developing RA after a long history of mastocytosis. Of great interest, antihistamine treatment alone was sufficient to treat RA in this patient.